2012
DOI: 10.1111/j.1538-7836.2011.04566.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancers in patients with hemophilia: a retrospective study from the Italian Association of Hemophilia Centers

Abstract: Summary.  Background: The increased life expectancy of the hemophilia population, primarily as a result of advances in factor replacement therapy, has enabled hemophiliacs to reach an older age. Consequently, age‐related diseases, such as cardiovascular disorders and cancers, are being increasingly recognized in such patients. However, only few data are available on such co‐morbidities, their management and impact on the primary bleeding disorders. Objectives: With the aim of investigating several still unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 18 publications
(26 reference statements)
2
25
4
1
Order By: Relevance
“…In this study, no bleeding complications were observed in PWH undergoing chemotherapy or radiotherapy. This observation contrasts that of an Italian series involving 122 PWH, in which bleeding complications occurred more often in patients receiving chemotherapy (14%) or radiotherapy (19%) than in those undergoing invasive (8%) or surgical procedures (0.2%). Most notably, in this published series, the patients treated by chemotherapy or radiotherapy were not given clotting factor concentrate prophylaxis.…”
Section: Discussioncontrasting
confidence: 82%
“…In this study, no bleeding complications were observed in PWH undergoing chemotherapy or radiotherapy. This observation contrasts that of an Italian series involving 122 PWH, in which bleeding complications occurred more often in patients receiving chemotherapy (14%) or radiotherapy (19%) than in those undergoing invasive (8%) or surgical procedures (0.2%). Most notably, in this published series, the patients treated by chemotherapy or radiotherapy were not given clotting factor concentrate prophylaxis.…”
Section: Discussioncontrasting
confidence: 82%
“…14 A previous study by Rabkin et al in 1992 showed that with the exception of Kaposi's sarcoma and Non-Hodgkin's lymphoma, cancer incidence was not increased in hemophilic HIV-positive patients compared to the general population of the United States. 15 Similar results were also seen in an Italian study by Tagliaferri et al 16 Our study showed that hemophilic HIV-positive patients were also at increased risk of cancers of the oral cavity, oropharynx and hypopharynx, and larynx when compared to the general population of Taiwan.…”
Section: To the Editorssupporting
confidence: 89%
“…As previously mentioned, the ubiquitous heat shock protein receptor LRP1/CD91 regulates signal transduction pathways and has been implicated in the pathogenesis of a number of human diseases. Thus, the LRP1/CD91 over-expression found in this study could help us to elucidate the molecular mechanisms underlying some of the still unexplained clinical findings recently observed in ageing haemophilia patients, such as the higher rates of hypertension and diabetes and lower mortality from ischaemic heart disease and cancers in comparison with the rates in the general, non-haemophilic population [22][23][24][25][26][27][28]. Indeed, a number of studies have documented that LRP1 is not only important for regulating vascular tone and smooth muscle cell proliferation, thus protecting from atherosclerosis [7,8], but it is also involved in the mechanisms of apoptosis and in the initiation of immune responses to tumours [29,30].…”
Section: Discussionmentioning
confidence: 99%